The Hyperglycemic and Anti-hyperlipidemic Properties of Honeybee Mixed with Wheat Germ in Streptozotocin-induced Diabetes in Rats - Nawal Abbas Tahoon; Rania Adel Eid
Aim: This study aimed to find out the impacts of a honeybee and Wheat Germ (WG) combination on blood glucose and cholesterol concentrations in diabetic rats when administered orally. Materials and Methods: Thirty-eight male Sprague Dawley rats were divided into normal (n=8) and diabetic (n=30). The second group was injected with streptozotocin (at a dose of 75 mg/ kg intraperitoneally), and those with blood glucose concentrations more than 250 mg/dL were classified as diabetic. Rats were divided into five groups, (1) non-diabetic group (n=8) received distilled water (2 mL/ day); (2) diabetic control group (n=8) received distilled water (2 mL/ day); (3) metformin diabetic group (n=7) received 2 mL of metformin drug solution (dose=100 mg/kg/day); (4) honeybee diabetic group (n=8) received honeybee solution (dose=2 g/kg/ day); and (5) wheat germ diabetic group (n=7) received 2 mL of honeybee (95 g) mixed with wheat germ (5 g) solution (dose= 2 g/kg/day). After 28 days, blood was collected, and serum was extracted to determine glucose, HbA1c, and blood lipids. Results: The results showed that honeybee alone and mixed with wheat germ increased blood glucose significantly above 350 mg/dL and HbA1c above 8.4%. Conversely, the administration of wheat germ caused a noteworthy decrease in total cholesterol, triglycerides, and LDL concentrations among rats with diabetes. Conclusion: Consuming honeybees alone and combined with wheat germ may lead to hyperglycemia. Conversely, consuming honeybees in combination with wheat germ may result in hypocholesterolemia. These results indicate that honeybee and wheat germ could be functional food for managing hyperlipidemia in diabetic patients.